Factors Affecting Malnutrition in Parkinson's Disease Patients Using Mini Nutritional Assessment at H. Adam Malik Hospital and Network Hospitals - Dwi Putri, Sabrina; Kadri, Alfansuri; Hutagalung, Haflin Soraya (Journal of Society Medicine, 2024)
Introduction: Parkinson's Disease (PD) is a progressive neurodegenerative disorder characterized by the loss of motor control due to the degeneration of dopamine neurons in the brain and the formation of Lewy bodies. The exact cause of PD is still unknown, but factors such as free radicals, mitochondrial dysfunction, and protein degradation are believed to play a role. To identify the factors that influence malnutrition in patients with Parkinson's disease. Method: This study is an observational analytical study with a cross-sectional design, conducted at RSUP H. Adam Malik Medan and its hospital network. The subjects were 45 Parkinson's patients selected consecutively from March to June 2024. The data in this study used primary data using the Mini Nutritional Assessment (MNA) questionnaire obtained from anamnesis, physical examination and nutritional status examination using body weight, height, calf circumference and upper arm circumference. Results: Statistical analysis showed no significant results between gender, therapy regimen, and symptoms such as bradykinesia, rigidity, hyposmia, and dysphagia on malnutrition with values of p = 0.157, p = 0.377, p = 0.173, p = 0.173, p = 0.264, and p = 0.154, respectively. However, the results of the statistical analysis showed significant results between age and malnutrition with a p-value of 0.003 and a substantial relationship between disease duration, severity, and symptoms such as postural instability and constipation on malnutrition with the same p-value of p <0.001. Conclusion: There was an association between age, disease duration, severity, and symptoms such as postural instability and constipation in Parkinson's disease patients with malnutrition status.